Association Between Soluble CD40 Ligand and Hypercholesterolemia in Children and Adolescents - Aynur Küçükçongar Yavaş; Tuba Fatma Eminoğlu; İlyas Okur; Arzu Aral; Alev Hasanoğlu; Leyla Tümer (Journal of Pediatric Research)
Aim: Coronary heart disease is one of the most common causes of death around the world. The pathological process of coronary heart disease like atherosclerosis starts in childhood. During this period thrombosis constitutes a high-risk factor. In this study, we investigated the effect of soluble CD40 ligand (sCD40L) and clotting activation on children and adolescents with hypercholesterolemia. Materials and Methods: Plasma levels of sCD40L, P-selectin, 8-hydroxy-2-deoxyguanosine (8-OHdG), and prothrombin fragment 1+2 [(F) 1+2] were determined in thirty-five hypercholesterolemic patients (20 girls and 15 boys; age, median: 13 years) and forty healthy normocholesterolemic subjects (28 girls and 12 boys; age, median: 13 years). Results: No significant differences were observed between the patient group and controls in terms of age, high-density lipoprotein (HDL) cholesterol, 8-OHdG, F1+2 (p>0.05). However, there were significant differences between the two groups with respect to total cholesterol, low-density lipoprotein (LDL) cholesterol, very LDL cholesterol, triglycerides, sCD40L and P-selectin (p<0.05), which were higher in the patient group than the controls. A positive correlation was observed between sCD40L and P-selectin (p<0.05) in accordance with the Spearman correlation analysis. The correlation coefficients were 0.735 in the patient group and 0.647 in the control group. But there was no significant correlation between sCD40L and total cholesterol, LDL-cholesterol, HDL-cholesterol, very LDL-cholesterol, triglycerides, 8-OHdG, F1+2 (p>0.05). Conclusion: We believe that future prospective studies to determine the increase in the level of sCD40L with a larger sample size of a pediatric population with dyslipidemias may be more helpful in predicting the risk of cardiovascular disease.